SIFAT FISIK DAN MEKANIK PAPAN KOMPOSIT DARI BATANG SINGKONG DAN LIMBAH PLASTIK BERDASARKAN PELAPISAN DAN KOMPOSISI BAHAN BAKU - Rita, Ronnika; Setyawati, Dina; Usman, Fadillah H. (Universitas Tanjungpura, 2015)
The study aims to determine the influence of coating and composition of raw materials to physical and mechanical properties of composite board from singkong trunk and plastic waste and to know the best treatment. Composite board size was 30 cm x 30 cm x 1 cm. The plastic waste function as an adhesive and mix in three layer of composite board. The face and back layer consist of 15% and in the core consist of 70% with a target density of 0,7 g/cm3. This study used factorial experiment in a random design complete with 2 factors. The factor consist of factor coating which consists of 2 subfaktor (coating with veneer and without veneer) and factor composition (singkong trunk: plastic waste) which consists of 3 subfaktor 40:60, 50:50, and 60:40. The pressure was done with hot press temperature 180 ºC for 10 minute with pessure ± 25 kg/cm². Evaluation the quality of physical and mechanical properties to standard JIS A 5908-2003. The result of research showed that all the composite board can fulfill the standard JIS A 5908-2003, except on MOE value of the composite board of coating with without veneer. The best value of composite board was achieved on composition 60% singkong trunk and 40% plastic waste with, coating veneer. Keywords: Coating, composite board, composition, physical and mechanical properties, plastic polypropylene, singkong trunk